Enhancing Muslim Charity Commitment for Donations: Does Perceived Value Influence? - Netta Agusti; Clara Sahfitri; Asep Suryaman (Perkumpulan Ahli Manajemen Dakwah Indonesia (PAMDI), 2025)
Purpose – The viability of Islamic charitable institutions is contingent upon the dedication of their benefactors. The present study aims to examine the effect of perceived value on Muslim charity commitment and to identify the factors that influence it. Design/methodology/approach – The approach used in this study is a quantitative approach, with the Pearson correlation method serving as the primary statistical tool. The data were collected through the administration of questionnaires distributed online to donors at Inisiatif Zakat Indonesia (IZI). The data analysis techniques employed included simple regression tests and coefficient of determination (R²) tests. Findings – The regression test analysis indicate a substantial and statistically significant relationship between perceived value and donor commitment, with a correlation value of r = 0.500. The regression equation Y = 11.122 + 0.500X demonstrates a direct correlation between an increase in perceived value and a concomitant increase in donor commitment, with a statistical significance of 0.500. The statistical significance of the relationship is confirmed by the p-value of 0.000, which is smaller than 0.05. Consequently, as the perceived value to the donor increases, so does their propensity to donate. A comprehensive analysis of the pertinent factors reveals three distinct categories: emotional, social, and quality factors. Furthermore, the R2 test results indicate a relationship between perceived value and variable donor commitment of 57.1%. The remaining 42.9% is influenced by other factors: trust, service satisfaction, transparency, accountability, identification with the organization, and previous experience. Research implications – This paper posits that it is imperative for the administrators of Islamic charitable institutions to attend to the needs of donors in the future. In addition to the religious obligation to give to one another, donors need to be informed about their contributions. Originality/value – The perceived value has been repeatedly tested at the organizational level. However, tests examining the influence of these variables on donor commitment in Islamic charities have been neglected.